2014
DOI: 10.1161/hypertensionaha.114.03757
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uric Acid Genetic Risk Score With Blood Pressure

Abstract: Abstract-High levels of serum uric acid are associated with hypertension in observational studies. The aim of this study was to investigate the association of uric acid gene variants with blood pressure. We studied 5791 participants aged ≥55 years from the Rotterdam Study. Thirty gene variants identified for serum uric acid level were used to compile genetic risk score (GRS). We used linear regression models to investigate the association of the uric acid GRS with systolic and diastolic blood pressure in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 27 publications
0
37
1
3
Order By: Relevance
“…The association did not attenuate after further adjustment for antihypertensive medication use and conventional cardiovascular risk factors. Noteworthy, in a subgroup analysis the association of UA GRS with systolic blood pressure was significantly stronger in participants (n = 885) on diuretic treatment ( P = .007) . In conclusion, higher UA GRS was associated with lower systolic and diastolic blood pressure, while diuretics treatment may modify the association of UA genetic risk score with systolic blood pressure .…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…The association did not attenuate after further adjustment for antihypertensive medication use and conventional cardiovascular risk factors. Noteworthy, in a subgroup analysis the association of UA GRS with systolic blood pressure was significantly stronger in participants (n = 885) on diuretic treatment ( P = .007) . In conclusion, higher UA GRS was associated with lower systolic and diastolic blood pressure, while diuretics treatment may modify the association of UA genetic risk score with systolic blood pressure .…”
Section: Methodsmentioning
confidence: 58%
“…Noteworthy, in a subgroup analysis the association of UA GRS with systolic blood pressure was significantly stronger in participants (n = 885) on diuretic treatment ( P = .007) . In conclusion, higher UA GRS was associated with lower systolic and diastolic blood pressure, while diuretics treatment may modify the association of UA genetic risk score with systolic blood pressure . The discrepancy between these findings and other studies could be explained in different ways .…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…In a study by Hughes et al [17], a uric acid genetic risk score was associated with improved renal function. However, in a further genetic risk score study, Sedaghat et al [18] found 30 gene variants that were associated with increased serum uric acid but with lower blood pressure. In that study, the results were sensitive to diuretic therapy, and there was no relationship between a SLC2A9 SNP and BP in patients not treated with diuretics.…”
Section: Genetic and Environmental Factors Associated With Serum Uricmentioning
confidence: 99%
“…However, many studies [17, 6672], even when largely powered, reached opposite conclusions, despite two of them showing an association of GRSs with gout [66, 71] (Table 3). The Rotterdam cohort showed a negative association between hyperuricaemic GRS and blood pressure, even stronger in patients receiving diuretics [69]. The use of several gene variants in the GRS increased the possibility that some of the included genes (or genes in linkage disequilibrium with them, which are not independently distributed during meiosis) had other effects than their soluble uric acid (SUA)-modulating property, a phenomenon called pleiotropy, which could be an important confounder.…”
Section: Hyperuricaemia and Cardiovascular And Renal Diseasesmentioning
confidence: 99%